2013
DOI: 10.4172/jfiv.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation Assays Correlate with Sperm Abnormal Morphology and the Pregnancy Outcome

Abstract: JFIV, an open access journal J o u rn al of Fe rt il iz a tio n: In V it ro-I V F-Worldw id e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…A total of 200 cells were evaluated on each slide Delbes et al, 2013;Fortunato et al, 2013). The sperm suspension was first centrifuged for 5 min at 300 g. The supernatant was discarded and the pellet was washed in phosphate-buffered saline (19 PBS), Sigma-Aldrich, SP, Brazil.…”
Section: Sperm Dna Fragmentation Detection (Tunel Methods)mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 200 cells were evaluated on each slide Delbes et al, 2013;Fortunato et al, 2013). The sperm suspension was first centrifuged for 5 min at 300 g. The supernatant was discarded and the pellet was washed in phosphate-buffered saline (19 PBS), Sigma-Aldrich, SP, Brazil.…”
Section: Sperm Dna Fragmentation Detection (Tunel Methods)mentioning
confidence: 99%
“…Samples were analyzed using a fluorescence inverted microscope Nikon Eclipse E200 (Nikon Corp., Tokyo, Japan). A total of 200 cells were evaluated on each slide Delbes et al, 2013;Fortunato et al, 2013). Cells with DNA damage were considered TUNEL positive (apoptotic) (Fig.…”
Section: Sperm Dna Fragmentation Detection (Tunel Methods)mentioning
confidence: 99%
“…Therefore, abnormal sperm chromatin may result in male infertility, recurrent abortion, increased congenital anomalies , testicular cancer in offsprings as well as assisted reproductive failure (6 , 7) . It was found that the compact structure of sperm nuclear chromatin is important for the protection of genetic integrity during transport of the paternal genome through the male and female reproductive tracts (8) .…”
Section: Introductionmentioning
confidence: 99%
“…The patient characteristics are shown in Table 1. Ovulation induction and embryology protocols and procedures have been published previously (Fishel et al, 2011). In the tested and treated group, if either or both of the couple were carriers of the M2 haplotype, the female received LMWH (enoxaparin: Clexane; Sanofi Winthrop, France) subcutaneously in a dose of 40 mg daily beginning on the day of oocyte retrieval for fresh embryo transfer or, on the day of frozen embryo transfer, and for a minimum of 12 weeks, with the recommendation to continue until term.…”
Section: Methodsmentioning
confidence: 99%